Integration Of The Servqual, IPA, And CSI Methods To Analysis Customers Satisfaction - Andi Andi; mohammad Jufriyanto (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
One of the supporting components in running a company is the quality of service delivered to customers. &T Express Benjeng was among the first freight forwarding firms to establish itself in Gresik Regency's Benjeng sub-district. Several trip merchants were identified in Benjeng Gresik District throughout time. As a consequence, the number of people using J&T Express Benjeng services is falling. J&T Express Benjeng had never studied customer satisfaction before doing this research; therefore, evaluating the quality of customer service was critical to remain in an increasingly competitive business environment. The Service Quality techniques, Importance Performance Analysis, and the Customer Satisfaction Index were used in this research. The biggest disparity, according to the results of this study, is in the reliability dimension, the assurance dimension, the responsiveness dimension, the empathy dimension, and the tangibles dimension . According to the Importance Performance research, nine question indicators in quadrant I must be emphasized if performance is to increase. The Expedition must increase the value of the Customer Satisfaction Index by prioritizing repairs in quadrant I of the IPA Kartesius diagram. The Customer Satisfaction Index result indicating that the customer is pleased. Keywords : Service Quality, Importance Performance Analysis, Customer Satisfaction Index, Customer Satisfaction, Customer Interests